Communication skills questionnaire for adolescents and adults: its reliability and validity - Sheinov, Viktor P. (Journal of the Belarusian State University. Sociology, 2024)
The study of communication skills has become particularly relevant due to the negative impact on representatives of different generations of their excessive use of smartphones and social networks. At the same time, the research actively uses the long-established test of communication skills for adolescents and high school students by Michelson, adapted in 1995 by Yu. Z. Gil’bukh. However, publications containing evidence of the reliability and validity of this questionnaire are not available. The objectives of this study are to prove the reliability and validity of the questionnaire of communication skills for adolescents and adults, to develop a reliable and valid abbreviated version of this questionnaire. The baseline data for the study were collected in Belarus and Russia mainly through an online survey of 1833 respondents, including 1122 adolescents aged 13–17 (601 girls and 521 boys) and 711 adults under the age of 82 (361 women and 350 men). As a result of the study, an abbreviated version of the communicative skills questionnaire for adolescents and adults was constructed, consisting of 26 questions. The abbreviated version of the questionnaire satisfies the main criteria for validity and reliability and has better psychometric characteristics than its original version. The practical significance of the study lies in the fact that the presence of a single toolkit will allow using it to conduct comparative studies of communicative skills simultaneously in different age categories.